Numerical solution of the dip coating process with insoluble surfactants: Langmuir or a linear approximation for surface tension? - Berli, Marcelo Eduardo (2013)
In this work the dip coating process when an insoluble surfactant is adsorbed at the interface is numerically studied. The work centers in the applicability of the linear approximation usually employed to model the relationship between surface tension and the concentration of the surface active agent. Reported solutions show that film thicknesses predicted with a linear model can differ significantly from those computed with a more reliable equation of state.